2020
DOI: 10.26444/aaem/115180
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and impact of back pain on the quality of life of healthcare workers

Abstract: Introduction and Objective. Back pain affects specific occupational groups, among which healthcare workers are the most predisposed. Therefore, the aim of this study was to determine the interdependences between subjective disability and their correlation with pain intensity and quality of life assessment among professionally active medical workers, taking into account working, socio-demographic and health conditions. Materials and Method. The cross-sectional study enrolled 110 professionally active medical wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
(33 reference statements)
0
16
1
2
Order By: Relevance
“…A study on primary healthcare workers in Brazil also reported that respondents presenting with negative self-perceived health status or being diagnosed with systemic illnesses by physicians contributed to poor physical health QoL (Teles et al, 2014). Moreover, a study on how chronic back pain affects the QoL of a cohort of medical workers also indicated that a greater degree of disability due to the medical condition was associated with poor physical health QoL (Mroczek et al, 2020). Hence, our findings further strengthened the reciprocal relationship between pre-existing medical conditions and poor physical health QoL.…”
Section: Discussionmentioning
confidence: 99%
“…A study on primary healthcare workers in Brazil also reported that respondents presenting with negative self-perceived health status or being diagnosed with systemic illnesses by physicians contributed to poor physical health QoL (Teles et al, 2014). Moreover, a study on how chronic back pain affects the QoL of a cohort of medical workers also indicated that a greater degree of disability due to the medical condition was associated with poor physical health QoL (Mroczek et al, 2020). Hence, our findings further strengthened the reciprocal relationship between pre-existing medical conditions and poor physical health QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence in this population is reported to be 60.98%-72% [4][5][6] and has resulted in frequent nursing staff resignations and absences due to ill health [7,8]. NSCLBP in nurses can lead to significantly reduced quality of life [9] and is detrimental to the development of the nursing team and patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Basic information used for the sample plots the thickness of the muscle;6 numerical rating scale, NRS; 7 SF-36 questionnaire;8 Japanese Orthopaedic Association, JOA scores;9 Oswestry disability index, ODI; 10 self-rating depression scale, SDS; 11 self-rating anxiety scale, SAS;12 feeling of fatigue;13 frequency of low back pain;14 World Health Organization Quality of Life-brief questionnaire, WHOQOL-BREF;15 Job satisfaction;16 preventive behavior score;17 self-efficacy;18 occurrence rate. A: Physical exercise; B: Physical exercise plus health education; C: Health education; D: Multidisciplinary intervention; E: Manipulation treatment; F: Manipulation treatment plus physical exercise; G: None; H: Yoga; I: Protective equipment; J: Low back exercise; K: Low back exercise plus health education; L: Self-management; M: Self-management plus health education.…”
mentioning
confidence: 99%
“…Birabi et al 9 relataram prevalência pontual de 67,1% entre agricultores. A maioria dos estudos disponíveis sobre lombalgia tem sido em populações trabalhadoras 10,11 ou são baseados em hospitais 12,13 levando a conclusões não representativas. Há uma escassez de dados epidemiológicos sobre DL de indivíduos no setor informal ou desempregados, especialmente em países de baixa renda 14 .…”
Section: Artigo Originalunclassified